The Impact of Teacher Training on The Academic Performance of Student's Among Secondary Schools in Mbarara District: A Case Study of Kashari County Uganda. - Amumpaire, Catherine (Kabale University, 2024)
The current educational system is mainly theoretical and examinations-oriented. The teaching and learning activities are geared towards making the learner able to respond to examinations and not necessarily creating solutions to problems that disturb the nation. Teachers on the other hand are trained to deliver content based on a fixed syllabus and cannot deviate from the same. The syllabus sometimes has outdated things that are not helpful to the current generation. Due to a lack of in-service training, the teachers continue to deliver content in a disorganized manner, and teacher-centered teaching and are not able to link class teaching to the immediate environment so that students can relate well. The effectiveness of teaching, availability of teaching resources, human resource availability, class size, and the distance to schools are also some of the factors that affect students' performance. Due to these hindrances in teaching and learning, the student's academic performance in national exams has been worsening in some subjects and always recording a negative deviation in many places all over the country. In this relation, therefore, the study sought to establish the relationship between teacher training and the academic performance of learners in Kashari County. The study aimed to investigate the impacts of teacher training on student performance, the extent the teacher's experience on the job improved performance, and the way teachers' commitment on the job improved performance in Kashari, Mbarara district. This study used the Kashari region as a case study with 30 schools from which a sample was selected. The study used 50 respondents who were obtained using a probabilistic sampling procedure and we're both teachers and owners of schools. Most of them agreed that training affects the performance of learners. This study also found that the years of experience of teachers and the commitment of these teachers also contributed much towards the performance of learners. However, this study also found that there are some other factors to which more attention should be put other than training and they included student factors, school factors, and family factors The research found out that some teachers were not trained at all and it recommended the stakeholders to begin investigating in training of the teachers as they affect the performance of learners. Therefore, there should be training in each school as it was found that some were not trained. This study would be very important to educational institutions all over the country, county, governments, the Ministry of Education (MoE), educational policymakers, school boards of management, and school head teachers and also form a baseline for further research